A Pragmatic Analysis of Politeness Strategies in Classroom Interaction - Syahrul Efendi Lubis; Dimas Setiawan; Gumarpi Rahis Pasaribu (Rahis Cendekia Indonesia, 2026)
This study aims to analyze the use of politeness strategies in classroom interaction from a pragmatic perspective. It focuses on identifying the types of politeness strategies employed by teachers and students, as well as examining their functions in facilitating effective communication. This research uses a qualitative approach with a descriptive design. The data were collected through classroom observation and documentation, including audio recordings of interaction between the teacher and students in an English as a Foreign Language (EFL) classroom. The participants consisted of one teacher and several students selected purposively based on their involvement in classroom interaction. The findings reveal that four types of politeness strategies are used in classroom interaction, namely bald on-record, positive politeness, negative politeness, and off-record strategies. Among these, positive politeness is the most frequently used strategy, particularly by the teacher, to build rapport and create a supportive learning atmosphere. The use of politeness strategies is influenced by social roles, power relations, and communicative purposes within the classroom. The study concludes that politeness strategies play an important role in maintaining effective communication and fostering a conducive learning environment. It is suggested that teachers incorporate pragmatic awareness into English language teaching to improve students’ communicative competence